CLINICAL EFFICACY OF VRAHAT DADIMASHTAK CHOORNA: A CRITICAL REVIEW - Kumar Khatik, *Rohit; Sharma, Anita; Subodh, Jain (International Journal of Ayurveda and Pharma Research, 2016)
According to Ayurvedic literature, the potency and efficacy (Saviryata awadhi) of Ayurvedic classical preparations depend upon quality of each drug (having Rasa panchak), desh (region), Kal (time), Ritu (season), their preparation method and route of administration. But now a day, in modern science got after research these concepts molded and depend on chemical composition of each drug or preparation. Here we describe the claims of Vrahat dadimashtak choorna in various diseases especially in Gastro-intestinal ailments. As per Acharya Sharangdhar, Vrahat dadimashtak choorna is useful for the treatment of following disorders:-Atisaar (diarrhoea) Kshaya (phthisis), Gulma (abdominal tumor/abdominal lump), Grahani (sprue), Galagraha (pain in throat), Mandagni (Improper digestion), Peenus (rhinitis), Kas (cough). The all contents of Vrahat dadimashtak choorna have been evaluated according to the research done by various research scholars. The efficacy has been also tested according to the Rasa, Guna, Virya, Vipaka described in Ayurvedic text. In this research paper we are try to establish the claims of old Ayurvedic text on the recent research parameters.